Thermoneutrality-Induced Macrophage Accumulation in Brown Adipose Tissue Does Not Impair the Tissue’s Competence for Cold-Induced Thermogenic Recruitment - Fischer, Alexander W.; de Jong, Jasper M. A.; Sass, Frederike; Schlein, Christian; Heeren, Joerg; Petrovic, Natasa (Frontiers in Endocrinology, 2020)
Brown adipose tissue from mice living under conditions approaching human thermal and nutritional conditions (prolonged exposure to thermoneutral temperature and to an energy-rich high-fat, high-sugar diet) - referred to as ‘physiologically humanized’ mice, displays morphological and molecular characteristics significantly different from those observed in young, chow-fed mice maintained at room temperature - referred to as ’standard’ mice. Here, we further examined brown fat from physiologically humanized and standard mice, as well as from mice exposed to thermoneutrality for a long time but not to an energy-rich diet - referred to here as ‘long-term thermoneutral’ mice. Global transcriptome analysis of brown fat revealed that genes that were the most upregulated in brown fat of thermoneutral mice (both physiologically humanized and long-term thermoneutral) were those related to inflammatory processes, including genes expressed selectively in macrophages. Cellular and molecular analyses confirmed that brown fat from thermoneutral mice was heavily infiltrated by macrophages, predominantly organized into crown-like structures. However, despite this, the brown fat of thermoneutral mice retained full competence to attain the greatest possible recruitment state and became macrophage-depleted during the process of cold acclimation. Thus, profound macrophage accumulation does not influence the thermogenic recruitment competence of brown fat.